Correlations between rail wear rates and operating conditions in a commercial railroad. (March 2016) - Santa, J.F; Toro, A.; Lewis, R.
Abstract: The rail wear rates per traffic unit (mm/MTon) in the curves of a 4.5 km-long commercial line over a period of 9 years were measured and related to specific operation conditions. The rail corrugation was analyzed using a Corrugation Analysis Trolley (CAT) and visual inspection was carried out in order to identify the defects in the railroad. Since Rolling Contact Fatigue (RCF), artificial abrasion and corrugation were found to be the most important issues the grinding procedures used during maintenance of the railroad were evaluated to assess their effectiveness on removing the defects from the rail surface. The results showed that the wear rates in the studied railroad were several times higher than those typically found in the literature, mainly as a consequence of inappropriate grinding regimes. White layer formation and only partial removal of cracks emerged as the most relevant drawbacks of rail grinding procedures. Highlights: The most important wear mechanisms in the studied railroad are: Rolling Contact Fatigue (RCF) and abrasion due to rail grinding. Practical use indexes were proposed to classify the rail wear rates (WR) as mild, (WR<0.06 mm/MTon), medium (0.06 mm/MTon<WR<0.2 mm/MTon) and severe (WR>0.2 mm/MTon). The contribution of inadequate rail grinding to the overall material removal is significant since it causes defects that act as a source of preferential nucleation sites for new cracks. The reprofiling procedures studied in this investigation produced a white layer with micro-cracks, which together with the strict grinding criteria used to control corrugation, explained the highest wear rates observed. The corrugation frequencies are in the range between 100 and 250 Hz, which typically corresponds to the excitation of the vertical dynamic behavior of the vehicle/track system. The presence of valleys on welds was also observed after the analysis of the profiles.